Surgical treatment of caseous calcification of the mitral annulus causing mitral stenosis and mimicking the clinical picture of infective endocarditis: A case report. Issue 4 (7th March 2023) - Kahraman, Nail; Topal, Dursun; Coşkun, Gültekin; Tiryakioğlu, Selma Kenar; Topal, Serra; Güler, Sena; Binicier, Nöfel Ahmet; Koca, Fatih; Demir, Deniz
Abstract: Among masses involving the mitral valve and annulus, caseous calcification of the mitral annulus (CCMA) is a rare disease. CCMA accounts for .63% of all mitral annular calcification (MAC) cases. The pathophysiology is still unknown. The correct diagnosis and treatment of this disease is very important to prevent complications. We present a case of giant CCMA with advanced mitral stenosis and hypertrophic cardiomyopathy, presenting with symptoms of infection and therefore a preliminary diagnosis of infective endocarditis. Because of these features, we wanted to share our case as it is the 1st case in the literature.